Endoplasmic reticulum stress inhibits AR expression via the PERK/eIF2α/ATF4 pathway in luminal androgen receptor triple-negative breast cancer and prostate cancer - Xiaoli Li; Duanfang Zhou; Yongqing Cai; Xiaoping Yu; Xiangru Zheng; Bo Chen; Wenjun Li; Hongfang Zeng; Moustapha Hassan; Ying Zhao; Weiying Zhou (npj Breast Cancer, 2022)
Abstract Androgen receptor (AR) is an important prognostic marker and therapeutic target in luminal androgen receptor triple-negative breast cancer (LAR TNBC) and prostate cancer (PCa). Endoplasmic reticulum (ER) stress may activate the unfolded protein response (UPR) to regulate associated protein expression and is closely related to tumor growth and drug resistance. The effect of ER stress on AR expression and signaling remains unclear. Here, we focused on the regulation and underlying mechanism of AR expression induced by ER stress in LAR TNBC and PCa. Western blotting and quantitative RT-PCR results showed that AR expression was markedly decreased under ER stress induced by thapsigargin and brefeldin A, and this effect was dependent on PERK/eIF2α/ATF4 signaling activation. Chromatin immunoprecipitation-PCR and luciferase reporter gene analysis results showed that ATF4 bound to the AR promoter regions to inhibit its activity. Moreover, ATF4 overexpression inhibited tumor proliferation and AR expression both in vitro and in vivo. Collectively, these results demonstrated that ER stress could decrease AR mRNA and protein levels via PERK/eIF2α/ATF4 signaling in LAR TNBC and PCa. Targeting the UPR may be a treatment strategy for AR-dependent TNBC and PCa.